First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Incentivising coastal wetland restoration: What factors influence private landholder participation in Australia? - Romy Greiner; A. Rifaee Rasheed; Maksym Polyakov; Melissa Wartman (Journal of Environmental Management, 2026)

Runoff and soil erosion on woodland-encroached sagebrush rangeland under simulated rainfall and concentrated flow conditions - Viktor O. Polyakov; C. Jason Williams; Justin C. Johnson; Erin L. Phelps; Raven Chavez; Philip Heilman; William A. Rutherford; Osama Z. Al-Hamdan; Sayjro K. Nouwakpo; Jia Hu; Kenneth E. Spaeth; Samuel Anderson (CATENA, 2026)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Protease S of entomopathogenic bacterium Photorhabdus laumondii: expression, purification and effect on greater wax moth Galleria mellonella - Anastasia O. Svetlova; Maria A. Karaseva; Igor M. Berdyshev; Ksenia N. Chukhontseva; Olga V. Pobeguts; Maria A. Galyamina; Igor P. Smirnov; Nikita B. Polyakov; Maria G. Zavialova; Sergey V. Kostrov; Ilya V. Demidyuk (Molecular Biology Reports, 2024)

Cytotoxic and ROS generation activity of anthraquinones chelate complexes with metal ions - Viktor A. Timoshnikov; Irina A. Slepneva; Olga A. Chinak; Olga Yu Selyutina; Nikolay E. Polyakov (BioMetals, 2024)

Analyzing the benefits and limitations of advanced 2,4-D herbicide delivery systems - Vera V. Butova; Tatiana V. Bauer; Vladimir A. Polyakov; Vishnu D. Rajput; Tatiana M. Minkina (Crop Protection, 2024)

Genetic Features of Tongue Cancer Recurrence in Young Adults - E. S. Kolegova; A. A. Schegoleva; R. S. Vorobev; I. K. Fedorova; D. E. Kulbakin; A. P. Polyakov; A. V. Mordovsky; L. P. Yakovleva; A. S. Vyalov; V. T. Tsiklauri; M. A. Kropotov; N. G. Suchkova; et al. (Bulletin of Experimental Biology and Medicine, 2024)

Application of X-ray based modern instrumental techniques to determine the heavy metals in soils, minerals and organic media - Mikhail V. Kirichkov; Vladimir A. Polyakov; Sudhir S. Shende; Tatiana M. Minkina; Dina G. Nevidomskaya; Ming Hung Wong; Tatiana V. Bauer; Victoria A. Shuvaeva; Saglara S. Mandzhieva; Victoria S. Tsitsuashvili (Chemosphere, 2024)

Assessment of the Spatial Resolution and Accuracy of Temperature Measurements in Radiothermometry of the Breast - M. V. Polyakov; A. V. Khoperskov; S. V. Agasieva; I. O. Porokhov (Biomedical Engineering, 2023)

Differential Markers of Subpopulations of Epithelial Cells of the Larynx in Squamous Cell Carcinoma - I. V. Arutyunyan; A. G. Soboleva; K. B. Gordon; D. S. Kudashkina; D. A. Miroshnichenko; A. P. Polyakov; I. V. Rebrikova; A. V. Makarov; A. V. Lokhonina; T. Kh. Fatkhudinov (Bulletin of Experimental Biology and Medicine, 2022)

Antibacterial Activity of Lactobacillus plantarum Supernatant on Non-Fermenting Gram-Negative Bacteria - T. A. Danilova; G. A. Danilina; A. A. Adzhieva; N. B. Polyakov; V. G. Zhukhovitskii (Bulletin of Experimental Biology and Medicine, 2022)

A Steady Regime of Volume and Heat Transports in the Eastern Arctic Ocean in the Early 21st Century - A. V. Pnyushkov; I. V. Polyakov; G. V. Alekseev; I. M. Ashik; T. M. Baumann; E. C. Carmack; V. V. Ivanov; R. Rember (Frontiers in Marine Science, 2021)
Mooring observations in the eastern Eurasian Basin of the Arctic Ocean showed that mean 2013–2018 along-slope volume and heat (calculated relative to the freezing temperature) transports in the upper 800 m were 4.8 ± 0.1 Sv (1 Sv = 10 6 m 3 /s) and 34.8 ± 0.6 TW, respectively. Volume and heat transports within the Atlantic Water (AW) layer (∼150–800 m) in 2013–2018 lacked significant temporal shifts at annual and longer time scales: averaged over the two periods of mooring deployment in 2013–2015 and 2015–2018, volume transports were 3.1 ± 0.1 Sv, while AW heat transports were 31.3 ± 1.0 TW and 34.8 ± 0.8 TW. Moreover, the reconstructed AW volume transports over longer, 2003–2018, period of time showed strong interannual variations but lacked a statistically significant trend. However, we found a weak positive trend of 0.08 ± 0.07 Sv/year in the barotropic AW volume transport estimated using dynamic ocean topography (DOT) measurements in 2003–2014 – the longest period spanned by the DOT dataset. Vertical coherence of 2013–2018 transports in the halocline (70–140 m) and AW (∼150–800 m) layers was high, suggesting the essential role of the barotropic forcing in constraining along-slope transports. Quantitative estimates of transports and their variability discussed in this study help identify the role of atlantification in critical changes of the eastern Arctic Ocean.

Corrigendum: Borealization of the Arctic Ocean in Response to Anomalous Advection From Sub-Arctic Seas - Igor V. Polyakov; Matthew B. Alkire; Bodil A. Bluhm; Kristina A. Brown; Eddy C. Carmack; Melissa Chierici; Seth L. Danielson; Ingrid Ellingsen; Elizaveta A. Ershova; Katarina Gårdfeldt; Randi B. Ingvaldsen; Andrey V. Pnyushkov; et al. (Frontiers in Marine Science, 2021)

Artificial Intelligence Technologies in the Diagnosis of Acute Lymphoblastic Leukemia and Minimal Residual Disease - V. G. Nikitaev; N. N. Tupitsyn; A. N. Pronichev; E. V. Polyakov; V. V. Dmitrieva; O. A. Chernysheva; I. N. Serebryakova; A. D. Palladina (Biomedical Engineering, 2021)

The Pan-Arctic Continental Slope: Sharp Gradients of Physical Processes Affect Pelagic and Benthic Ecosystems - Bodil A. Bluhm; Markus A. Janout; Seth L. Danielson; Ingrid Ellingsen; Maria Gavrilo; Jacqueline M. Grebmeier; Russell R. Hopcroft; Katrin B. Iken; Randi B. Ingvaldsen; Lis L. Jørgensen; Ksenia N. Kosobokova; Ron Kwok; et al. (Frontiers in Marine Science, 2020)
Continental slopes – steep regions between the shelf break and abyssal ocean – play key roles in the climatology and ecology of the Arctic Ocean. Here, through review and synthesis, we find that the narrow slope regions contribute to ecosystem functioning disproportionately to the size of the habitat area (∼6% of total Arctic Ocean area). Driven by inflows of sub-Arctic waters and steered by topography, boundary currents transport boreal properties and particle loads from the Atlantic and Pacific Oceans along-slope, thus creating both along and cross-slope connectivity gradients in water mass properties and biomass. Drainage of dense, saline shelf water and material within these, and contributions of river and meltwater also shape the characteristics of the slope domain. These and other properties led us to distinguish upper and lower slope domains; the upper slope (shelf break to ∼800 m) is characterized by stronger currents, warmer sub-surface temperatures, and higher biomass across several trophic levels (especially near inflow areas). In contrast, the lower slope has slower-moving currents, is cooler, and exhibits lower vertical carbon flux and biomass. Distinct zonation of zooplankton, benthic and fish communities result from these differences. Slopes display varying levels of system connectivity: (1) along-slope through property and material transport in boundary currents, (2) cross-slope through upwelling of warm and nutrient rich water and down-welling of dense water and organic rich matter, and (3) vertically through shear and mixing. Slope dynamics also generate separating functions through (1) along-slope and across-slope fronts concentrating biological activity, and (2) vertical gradients in the water column and at the seafloor that maintain distinct physical structure and community turnover. At the upper slope, climatic change is manifested in sea-ice retreat, increased heat and mass transport by sub-Arctic inflows, surface warming, and altered vertical stratification, while the lower slope has yet to display evidence of change. Model projections suggest that ongoing physical changes will enhance primary production at the upper slope, with suspected enhancing effects for consumers. We recommend Pan-Arctic monitoring efforts of slopes given that many signals of climate change appear there first and are then transmitted along the slope domain.

Effect of Glycyrrhizic Acid and Arabinogalactan on the Membrane Potential of Rat Thymocytes Studied by Potential-Sensitive Fluorescent Probe - Yuri I. Glazachev; Anna A. Schlotgauer; Viktor A. Timoshnikov; Polina A. Kononova; Olga Yu. Selyutina; Ekaterina A. Shelepova; Maxim V. Zelikman; Mikhail V. Khvostov; Nikolay E. Polyakov (The Journal of Membrane Biology, 2020)

Primary 3D Culture of Human Thyroid Follicle-Like Structures in Platelet Lysate-Based Gel - N. S. Sergeeva; V. A. Kirsanova; Yu. D. Khesuani; I. K. Sviridova; T. E. Skachkova; V. A. Mironov; A. P. Polyakov; A. D. Kaprin (Bulletin of Experimental Biology and Medicine, 2020)

Borealization of the Arctic Ocean in Response to Anomalous Advection From Sub-Arctic Seas - Igor V. Polyakov; Matthew B. Alkire; Bodil A. Bluhm; Kristina A. Brown; Eddy C. Carmack; Melissa Chierici; Seth L. Danielson; Ingrid Ellingsen; Elizaveta A. Ershova; Katarina Gårdfeldt; Randi B. Ingvaldsen; Andrey V. Pnyushkov; et al. (Frontiers in Marine Science, 2020)
An important yet still not well documented aspect of recent changes in the Arctic Ocean is associated with the advection of anomalous sub-Arctic Atlantic- and Pacific-origin waters and biota into the polar basins, a process which we refer to as borealization. Using a 37-year archive of observations (1981–2017) we demonstrate dramatically contrasting regional responses to atlantification (that part of borealization related to progression of anomalies from the Atlantic sector of sub-Arctic seas into the Arctic Ocean) and pacification (the counterpart of atlantification associated with influx of anomalous Pacific waters). Particularly, we show strong salinification of the upper Eurasian Basin since 2000, with attendant reductions in stratification, and potentially altered nutrient fluxes and primary production. These changes are closely related to upstream conditions. In contrast, pacification is strongly manifested in the Amerasian Basin by the anomalous influx of Pacific waters, creating conditions favorable for increased heat and freshwater content in the Beaufort Gyre halocline and expansion of Pacific species into the Arctic interior. Here, changes in the upper (overlying) layers are driven by local Arctic atmospheric processes resulting in stronger wind/ice/ocean coupling, increased convergence within the Beaufort Gyre, a thickening of the fresh surface layer, and a deepening of the nutricline and deep chlorophyll maximum. Thus, a divergent (Eurasian Basin) gyre responds altogether differently than does a convergent (Amerasian Basin) gyre to climate forcing. Available geochemical data indicate a general decrease in nutrient concentrations Arctic-wide, except in the northern portions of the Makarov and Amundsen Basins and northern Chukchi Sea and Canada Basin. Thus, changes in the circulation pathways of specific water masses, as well as the utilization of nutrients in upstream regions, may control the availability of nutrients in the Arctic Ocean. Model-based evaluation of the trajectory of the Arctic climate system into the future suggests that Arctic borealization will continue under scenarios of global warming. Results from this synthesis further our understanding of the Arctic Ocean’s complex and sometimes non-intuitive Arctic response to climate forcing by identifying new feedbacks in the atmosphere-ice-ocean system in which borealization plays a key role.

An Optimized k-Space Configuration for Parallel MRI Reconstruction - M. A. Pugachevskii; A. G. Polyakov (Biomedical Engineering, 2020)

HINT1 gene pathogenic variants: the most common cause of recessive hereditary motor and sensory neuropathies in Russian patients - O. A. Shchagina; T. B. Milovidova; A. F. Murtazina; G. E. Rudenskaya; S. S. Nikitin; E. L. Dadali; A. V. Polyakov (Molecular Biology Reports, 2020)

Peculiarities of Pharmacokinetics and Bioavailability of Some Cardiovascular Drugs under Conditions of Antiorthostatic Hypokinesia - A. V. Polyakov; A. A. Svistunov; S. N. Kondratenko; I. V. Kovachevich; L. G. Repenkova; M. I. Savelyeva; V. G. Kukes (Bulletin of Experimental Biology and Medicine, 2020)

The study of the full spectrum of variants leading to hyperphenylalaninemia have revealed 10 new variants in the PAH gene - I. Kuznetcova; P. Gundorova; O. Ryzhkova; A. Polyakov (Metabolic Brain Disease, 2019)

Automated Analysis of the Pigment Network in Dermatoscopic Images of Melanocytic Skin Tumors - V. G. Nikitaev; A. N. Pronichev; O. B. Tamrazova; V. Yu. Sergeev; Yu. Yu. Sergeev; A. V. Kozyreva; E. V. Polyakov; E. A. Druzhinina (Biomedical Engineering, 2019)

Antimicrobial Activity of Supernatant of Lactobacillus plantarum against Pathogenic Microorganisms - Т. A. Danilova; A. A. Adzhieva; G. A. Danilina; N. B. Polyakov; A. I. Soloviev; V. G. Zhukhovitsky (Bulletin of Experimental Biology and Medicine, 2019)

Effective inhibition of copper-catalyzed production of hydroxyl radicals by deferiprone - V. A. Timoshnikov; T. Kobzeva; O. Y. Selyutina; N. E. Polyakov; G. J. Kontoghiorghes (JBIC Journal of Biological Inorganic Chemistry, 2019)

Prognostic Risk Models for the Development of Cardiovascular Dysfunction in Adolescents with Essential Hypertension - A. S. Kosovtseva; Т. А. Bairova; L. V. Rychkova; V. M. Polyakov; L. I. Kolesnikova (Bulletin of Experimental Biology and Medicine, 2019)

In Vivo Experimental Study of Biological Compatibility of Tissue Engineered Tracheal Construct in Laboratory Primates - I. V. Gilevich; A. S. Sotnichenko; D. D. Karal-ogly; E. A. Gubareva; E. V. Kuevda; I. S. Polyakov; B. A. Lapin; S. V. Orlov; V. A. Porkhanov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2018)

Comparative Study of Novel Fluorescent Cyanine Nucleotides: Hybridization Analysis of Labeled PCR Products Using a Biochip - V. E. Shershov; S. A. Lapa; V. E. Kuznetsova; M. A. Spitsyn; T. O. Guseinov; S. A. Polyakov; A. A. Stomahin; A. S. Zasedatelev; A. V. Chudinov (Journal of Fluorescence, 2017)

Morphological Analysis of Biocompatibility of Autologous Bone Marrow Mononuclear Cells with Synthetic Polyethylene Terephthalate Scaffold - I. V. Gilevich; I. S. Polyakov; V. A. Porkhanov; V. P. Chekhonin (Bulletin of Experimental Biology and Medicine, 2017)

Production and Analysis of Biological Properties of Recombinant Human Apolipoprotein A-I - A. V. Ryabchenko; M. V. Kotova; N. V. Tverdohleb; R. A. Knyazev; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2015)

Is It Possible to Predict Strong Earthquakes? - Y. S. Polyakov; G. V. Ryabinin; A. B. Solovyeva; S. F. Timashev (Pure and Applied Geophysics, 2015)

Content of Circulating Extracellular DNA, Plasma Activities of Matrix Metalloproteinases, and Ultrastructure of the Myocardium in Hypothyroid Rats with Hypercholesterolemia - L. M. Polyakov; E. L. Lushnikova; A. A. Karpova; G. S. Russkikh; O. N. Poteryaeva; D. B. Nikityuk; L. M. Nepomnyashchikh; Zh. I. Belonogova; D. V. Sumenkova; R. D. Nepomnyashchikh; V. I. Pichigin (Bulletin of Experimental Biology and Medicine, 2015)

Characterizing Spatial Uncertainty when Integrating Social Data in Conservation Planning - A. M. Lechner; C. M. Raymond; V. M. Adams; M. Polyakov; A. Gordon; J. R. Rhodes; M. Mills; A. Stein; C. D. Ives; E. C. Lefroy (Conservation Biology, 2014)
Recent conservation planning studies have presented approaches for integrating spatially referenced social (SRS) data with a view to improving the feasibility of conservation action. We reviewed the growing conservation literature on SRS data, focusing on elicited or stated preferences derived through social survey methods such as choice experiments and public participation geographic information systems. Elicited SRS data includes the spatial distribution of willingness to sell, willingness to pay, willingness to act, and assessments of social and cultural values. We developed a typology for assessing elicited SRS data uncertainty which describes how social survey uncertainty propagates when projected spatially and the importance of accounting for spatial uncertainty such as scale effects and data quality. These uncertainties will propagate when elicited SRS data is integrated with biophysical data for conservation planning and may have important consequences for assessing the feasibility of conservation actions. To explore this issue further, we conducted a systematic review of the elicited SRS data literature. We found that social survey uncertainty was commonly tested for, but that these uncertainties were ignored when projected spatially. Based on these results we developed a framework which will help researchers and practitioners estimate social survey uncertainty and use these quantitative estimates to systematically address uncertainty within an analysis. This is important when using SRS data in conservation applications because decisions need to be made irrespective of data quality and well characterized uncertainty can be incorporated into decision theoretic approaches.

Heat loss from the Atlantic water layer in the northern Kara Sea: causes and consequences - I. A. Dmitrenko; S. A. Kirillov; N. Serra; N. V. Koldunov; V. V. Ivanov; U. Schauer; I. V. Polyakov; D. Barber; M. Janout; V. S. Lien; M. Makhotin; Y. Aksenov (Ocean Science, 2014)
A distinct, subsurface density front along the eastern St. Anna Trough in the northern Kara Sea is inferred from hydrographic observations in 1996 and 2008–2010. Direct velocity measurements show a persistent northward subsurface current (~ 18 cm s−1) along the St. Anna Trough eastern flank. This sheared flow, carrying the outflow from the Barents and Kara seas to the Arctic Ocean, is also evident from shipboard observations as well as from geostrophic velocities and numerical model simulations. Although we cannot substantiate our conclusions by direct observation-based estimates of mixing rates in the area, we hypothesize that the enhanced vertical mixing along the St. Anna Trough eastern flank favors the upward heat loss from the intermediate warm Atlantic water layer. Modeling results support this hypothesis. The upward heat flux inferred from hydrographic data and model simulations is of O(30–100) W m−2. The region of lowered sea ice thickness and concentration seen both in sea ice remote sensing observations and model simulations marks the Atlantic water pathway in the St. Anna Trough and adjacent Nansen Basin continental margin. In fact, the sea ice shows a delayed freeze-up onset during fall and a reduction in the sea ice thickness during winter. This is consistent with our results on the enhanced Atlantic water heat loss along the Atlantic water pathway in the St. Anna Trough.

Halocline water modification and along-slope advection at the Laptev Sea continental margin - D. Bauch; S. Torres-Valdes; I. Polyakov; A. Novikhin; I. Dmitrenko; J. McKay; A. Mix (Ocean Science, 2014)
A general pattern in water mass distribution and potential shelf–basin exchange is revealed at the Laptev Sea continental slope based on hydrochemical and stable oxygen isotope data from the summers 2005–2009. Despite considerable interannual variations, a frontal system can be inferred between shelf, continental slope and central Eurasian Basin waters in the upper 100 m of the water column along the continental slope. Net sea-ice melt is consistently found at the continental slope. However, the sea-ice meltwater signal is independent from the local retreat of the ice cover and appears to be advected from upwind locations. In addition to the along-slope frontal system at the continental shelf break, a strong gradient is identified on the Laptev Sea shelf between 122° E and 126° E with an eastward increase of riverine and sea-ice related brine water contents. These waters cross the shelf break at ~ 140° E and feed the low-salinity halocline water (LSHW, salinity S

Nature-inspired soluble iron-rich humic compounds: new look at the structure and properties - Tatiana A. Sorkina; Alexander Yu. Polyakov; Natalia A. Kulikova; Anastasia E. Goldt; Olga I. Philippova; Alina A. Aseeva; Alexey A. Veligzhanin; Yan V. Zubavichus; Denis A. Pankratov; Eugene A. Goodilin; Irina V. Perminova (Journal of Soils and Sediments, 2014)

The Brain’s Error-Detecting Mechanism – a PET Study - M. V. Kireev; A. D. Korotkov; Yu. I. Polyakov; A. D. Anichkov; S. V. Medvedev (Neuroscience and Behavioral Physiology, 2013)

Cross-correlation earthquake precursors in the hydrogeochemical and geoacoustic signals for the Kamchatka peninsula - Gennadiy V. Ryabinin; Valeriy A. Gavrilov; Yuriy S. Polyakov; Serge F. Timashev (Acta Geophysica, 2012)

Vertical structure of recent arctic warming from observed data and reanalysis products - Vladimir A. Alexeev; Igor Esau; Igor V. Polyakov; Sarah J. Byam; Svetlana Sorokina (Climatic Change, 2012)

High-pressure neutron diffraction study on H–D isotope effects in brucite - Juske Horita; António M. dos Santos; Christopher A. Tulk; Bryan C. Chakoumakos; Veniamin B. Polyakov (Physics and Chemistry of Minerals, 2010)

North Atlantic warming: patterns of long-term trend and multidecadal variability - Igor V. Polyakov; Vladimir A. Alexeev; Uma S. Bhatt; Evgenia I. Polyakova; Xiangdong Zhang (Climate Dynamics, 2010)

North Atlantic warming: patterns of long-term trend and multidecadal variability - Igor V. Polyakov; Vladimir A. Alexeev; Uma S. Bhatt; Evgenia I. Polyakova; Xiangdong Zhang (Climate Dynamics, 2010)

Effect of Apolipoprotein A-I Complex with Tetrahydrocortisone on Protein Biosynthesis and Glucose Absorption by Rat Hepatocytes - D. V. Sumenkova; R. A. Knyazev; R. S. Guschya; L. M. Polyakov; L. E. Panin (Bulletin of Experimental Biology and Medicine, 2009)

A New Genetic Variant of MDX Mice: Study of the Phenotype - L. I. Krivov; M. A. Stenina; V. N. Yarygin; A. V. Polyakov; V. I. Savchuk; S. A. Obrubov; N. V. Komarova (Bulletin of Experimental Biology and Medicine, 2009)

Interaction of apolipoproteins A-I and E in the regulation of DNA, RNA, and protein biosynthesis in cultured rat hepatocytes - L. E. Panin; D. V. Sumenkova; R. A. Knyazev; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2007)

Effect of complexes of apolipoprotein A-I with tetrahydrocortisol and pregnenolone on protein biosynthesis in rat hepatocytes culture - L. E. Panin; R. A. Knyazev; D. V. Sumenkova; L. M. Polyakov (Bulletin of Experimental Biology and Medicine, 2007)

Identification of all pachytene bivalents in the common shrew using DAPI-staining of synaptonemal complex spreads - N. M. Belonogova; T. V. Karamysheva; L. S. Biltueva; E. A. Perepelov; J. M. Minina; A. V. Polyakov; N. S. Zhdanova; N. B. Rubtsov; J. B. Searle; P. M. Borodin (Chromosome Research, 2006)

GH-1 gene splicing mutations: Molecular basis of hereditary isolated growth hormone deficiency in children - O. V. Fofanova; O. V. Evgrafov; A. V. Polyakov; V. A. Peterkova; I. I. Dedov (Bulletin of Experimental Biology and Medicine, 2006)

Origin of the Permian-Triassic komatiites, northwestern Vietnam - Eero Hanski; Richard J. Walker; Hannu Huhma; Gleb V. Polyakov; Pavel A. Balykin; Tran Trong Hoa; Ngo Thi Phuong (Contributions to Mineralogy and Petrology, 2004)

Detection of Mutant Mycoplasma hominis Strains Resistant to 16-Membered Macrolide Antibiotic Josamycin in Clinical Samples - A. E. Karamova; A. V. Polyakov; N. V. Komarova (Bulletin of Experimental Biology and Medicine, 2004)

The Use of Homeopathic Preparation Vozraston in the Therapy of Patients with Rheumatoid Arthritis - S. M. Noskov; A. V. Snigireva; L. N. Dolgova; M. A. Somova; D. P. Polyakov (Bulletin of Experimental Biology and Medicine, 2003)

Development and Clinical Experience with a Computer Monitoring System Used at the Intensive Cardiological Care Unit - N. I. Kalyadin; V. A. Lemenkov; A. V. Korobeinikov; S. M. Perevozchikov; E. G. Odiyankov; A. N. Rodionov; V. F. Polyakov; S. M. Kotkov (Biomedical Engineering, 2002)